2022
DOI: 10.3389/fpls.2021.809558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Seasonal Climatic Variations on the Accumulation of Fruit Volatiles in Four Grape Varieties Under the Double Cropping System

Abstract: The double cropping system has been widely applied in many subtropical viticultural regions. In the 2-year study of 2014–2015, four grape varieties were selected to analyze their fruit volatile compounds in four consecutive seasons in the Guangxi region of South China, which had a typical subtropical humid monsoon climate. Results showed that berries of winter seasons had higher concentrations of terpenes, norisoprenoids, and C6/C9 compounds in “Riesling,” “Victoria,” and “Muscat Hamburg” grapes in both of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(70 reference statements)
2
5
0
Order By: Relevance
“…The C6 aldehyde levels in the six grape types at harvest in 2020 varied between 174.93 and 469.86 μg/L. In line with our results, Lu et al [26] found C6 aldehyde concentrations were different in summer and winter, suggesting that the yearly variation in C6 aldehyde leves in grapes might be due to seasonal weather differences, necessitating additional research.…”
Section: Green Leaf Volatile Evolutionsupporting
confidence: 89%
See 1 more Smart Citation
“…The C6 aldehyde levels in the six grape types at harvest in 2020 varied between 174.93 and 469.86 μg/L. In line with our results, Lu et al [26] found C6 aldehyde concentrations were different in summer and winter, suggesting that the yearly variation in C6 aldehyde leves in grapes might be due to seasonal weather differences, necessitating additional research.…”
Section: Green Leaf Volatile Evolutionsupporting
confidence: 89%
“…Except for those of Chardonnay and Cabernet Franc, the total C6 alcohol and acetate contents of the 2020 grapes were significantly lower than those of the 2019 harvest, which was possibly related to climate differences. A warmer climate facilitates the transformation of free C6 aldehydes into C6 alcohols, which generally have higher herbaceous odour thresholds (negative aroma) than the corresponding aldehydes [26]. Additionally, alcohols are more likely to form esters, thereby minimizing the herbaceous characteristics of aldehydes and maximizing the fruity characteristics of esters [25].…”
Section: Green Leaf Volatile Evolutionmentioning
confidence: 99%
“…However, Meng et al (2020) found that the high temperature (37 °C) repressed the activity of the VvCCD4b promoter. In a previous study reported by our research team ( Lu et al, 2022a ), the Muscat Hamburg and Victoria grapes had a lower norisoprenoid concentration in the summer season characterized by high temperature under the double cropping system. However, the opposite result was found in the Cabernet Sauvignon grapes that the winter season berries had a higher norisoprenoid concentration than the summer season berries.…”
Section: Resultsmentioning
confidence: 55%
“…Moreover, low temperatures during winter induced the upregulation of the genes VviDXSs, VviPSYs, and VviCCDs, which contribute to the accumulation of terpenes and norisoprenoids in winter berries. 55 Illumination Light conditions have a significant effect on volatile compounds in fruits. Different colors of light have different effects on aroma compounds, resulting in significant differences in fruit aroma.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
“…For example, the levels of hexanal, γ ‐terpinene, terpinol‐4‐ol, cis ‐furan linalool oxide, and trans ‐pyran linalool oxide in grapes were negatively correlated with time exposed to high temperatures. Moreover, low temperatures during winter induced the upregulation of the genes VviDXS s, VviPSY s, and VviCCD s, which contribute to the accumulation of terpenes and norisoprenoids in winter berries 55 …”
Section: Factors Affecting Fruit Aroma Synthesismentioning
confidence: 99%